2019
DOI: 10.1101/809053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential Outbreak in Brazil by Equine Herpesvirus Type 2 (EHV-2): Detection, Clinical and Genetic Analysis of Equine Gammaherpesvirus 2

Abstract: Equine herpesvirus (EHV) commonly affects horses causing neurologic and respiratory symptoms beside spontaneous abortions, meaning huge economic losses for equine industry worldwide. In foals the virus can facilitate secondary infections by Rhodococcus equi, important in morbidity and mortality in equines. A total of five genotypes of EHV were previously described in Brazil including EHV-1, EHV-2, EHV-3, EHV-4 and EHV-5. EHV-2 genotype had only been previously described in Brazil in asymptomatic animals. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Another types of herpesvirus are known causing distinct diseases and clinical signs in horses: equid alphaherpesvirus 1 (EHV-1), genus Varicellovirus, causing abortions in mares and also keratoconjunctivitis, encephalomyelitis, and neonatal pneumonia (Léon et al 2008, Dubale 2017, Estima-Silva et al 2019, Dunuwille et al 2020; equid gammaherpesvirus 2 (EHV-2), genus Percavirus, that has been found in horses with keratoconjunctivitis, gastroesophageal ulcers, and chronic throat lesions (Agius & Studdert 1994, Kershaw et al 2001, Cicolo et al 2019, Taulescu et al 2021; equid alphaherpesvirus 4 (EHV-4), genus Varicellovirus, an important cause of acute and fatal rhinopneumonithis in fowls and occasionally associated with equine abortions (Crabb & Studdert 1995, Gerst et al 2003; and equid gammaherpesvirus 5 (EHV-5), genus Percavirus, the cause of a severe and progressive syndrome of pulmonary fibrosis in adult horses (Verryken et al 2010, Williams et al 2013, Marenzoni et al 2015, Gulati et al 2019. A sixth virus, equid alphaherpesvirus 9 (EHV-9), genus Varicellovirus can cause subclinical encephalitides in horses, but until to date the disease was described just under experimental conditions (Hussey et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Another types of herpesvirus are known causing distinct diseases and clinical signs in horses: equid alphaherpesvirus 1 (EHV-1), genus Varicellovirus, causing abortions in mares and also keratoconjunctivitis, encephalomyelitis, and neonatal pneumonia (Léon et al 2008, Dubale 2017, Estima-Silva et al 2019, Dunuwille et al 2020; equid gammaherpesvirus 2 (EHV-2), genus Percavirus, that has been found in horses with keratoconjunctivitis, gastroesophageal ulcers, and chronic throat lesions (Agius & Studdert 1994, Kershaw et al 2001, Cicolo et al 2019, Taulescu et al 2021; equid alphaherpesvirus 4 (EHV-4), genus Varicellovirus, an important cause of acute and fatal rhinopneumonithis in fowls and occasionally associated with equine abortions (Crabb & Studdert 1995, Gerst et al 2003; and equid gammaherpesvirus 5 (EHV-5), genus Percavirus, the cause of a severe and progressive syndrome of pulmonary fibrosis in adult horses (Verryken et al 2010, Williams et al 2013, Marenzoni et al 2015, Gulati et al 2019. A sixth virus, equid alphaherpesvirus 9 (EHV-9), genus Varicellovirus can cause subclinical encephalitides in horses, but until to date the disease was described just under experimental conditions (Hussey et al 2021).…”
Section: Introductionmentioning
confidence: 99%